This is a typical mixture problem where using a table is the best thing.
pints juice % juice = total % juice
juice A x .70 = .70x
juice B 60-x .95 = .95(60-x)
total 60 .75 = 60(.75)
The last row gives you a total that you need to use, so do that multiplication to get 45. You now to need to add the last columns together for rows 1 and 2 and set them equal to 45: .7x +.95(60-x) = 45. When you do that math, you'll get that x = 48. This means that you need 48 pints of juice A and 60-48 pints of juice B, which is 12 pints.
Answer:
The process of finding the derivative of dependent variable in an implicit function by differentiating each term separately by expressing the derivative of the dependent variable as a symbol and by solving the resulting expression for the symbol.
Solve for c :
x⁴ + cx² + 100 = 0
cx² = -(x⁴ + 100)
c = - (x⁴ + 100)/x²
If x = 0, the right side is undefined and c would have no solution.
<span>a1= (which is the first term.)
to find the 2nd term you plug in 2 for (an) in the formula given to you. =-4(2-1)^2 *remember an represents the term u are looking for *
now you start to solve it
-4(2-1)^2
-4 (1)^2
.
-4^2
= 16
so your first two terms are 2 and 16 .</span>
I believe B . Because it seems equivalent